Development and optimization of a HS-SPME-GC-MS methodology to quantify volatile carbonyl compounds in Port wines - Moreira, Nathalie (2018)
A method based on headspace solid-phase microextraction (HS-SPME) coupled to gas chromatography-triple quadrupole/mass spectrometry detection (GC-TQ/MS) with a prior derivatization step with O-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine hydrochloride (PFBHA) was developed to quantify carbonyl compounds in different categories of Port wines. Optimal extraction conditions were obtained incubating 2 ml of wine with 2.3 g/l of PFBHA for 10 min and extracted during 20 min at 32 °C. The method was validated for 38 carbonyl compounds (alkanals, alkenals, Strecker aldehydes, dialdehydes, ketones and furan aldehydes) with regard to linearity, repeatability, inter and intra-day precision and accuracy, showing that the method is suitable for the determination of carbonyl compounds in wines. Tawny wines with ‘indication of age’ (10–40 years old) presented the highest levels of some carbonyl compounds, such as propanal, pentanal, hexanal, Strecker aldehydes, diacetyl, methyl glyoxal, 3-pentanone and 2-furfural, whereas Ruby wines were characterized by the highest amounts of some unidentified compounds.